Comparison of Chemical Constituents and Pharmacological Effects of Different Varieties of Chrysanthemum Flos in China. Issue 8 (1st July 2021) - Chen, Le; Liu, Yin; Huang, Xianju; Zhu, Yunyun; Li, Jinxin; Miao, Yuhuan; Du, Hongzhi; Liu, Dahui
Abstract: Chrysanthemum Flos is the prestigious traditional Chinese medicinal material and the popular health drink. This article comprehensively evaluated the chemical constituents, antioxidant activity, and hepatoprotective effects of 25 common chrysanthemum varieties in China. Firstly, we analyzed the chemical compositions of water extracts of chrysanthemum using UPLC/Q‐TOF‐MS, and identified 29 chemical components. The results displayed that chrysanthemum was rich in chemical constituents, but there were significant differences in the contents of four phenolic acids and five flavonoids among different varieties, and the coefficient of variation (CVs) ranged from 35.96 % to 114.62 %. Then, the antioxidant activities of different chrysanthemums were investigated, respectively via 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH), 2, 2'‐azinobis(3‐ethylbenzothiazoline‐6‐sulphonic acid) (ABTS), and Ferric Reducing Antioxidant Power (FRAP) assays. The spectrum‐effect relationships between nine main components and antioxidant activities were investigated to identify the antioxidant constitutes in chrysanthemums. Meanwhile, H2 O2 ‐induced hepatocyte injury testing showed wide variation in cultivar antioxidant capacity, with Tongchengju (TCJ) producing the best effect (90.32 %), followed by Chuju (CJ; 85.78 %). In addition, the hepatoprotective effects of 8 mainstream varieties were determined by the model of acute alcoholic liver injury. They protected liver from injury by affecting relevant liver function and antioxidant indexes. Huangshangongju (HSG) could decrease aspartate aminotransferase (AST) activity by 39.27 % in liver tissue; Hangju‐Fubaiju (HJ‐FBJ), Jinsihuangju (JSH), and Chuju (CJ) significantly decreased the malondialdehyde (MDA) content of liver tissue, which reduced by more than 40 %; Jinsihuangju (JSH) of used for tea could double the content of glutathione (GSH) and had the similar effect on superoxide dismutase (SOD) as the positive group, showing significant antioxidant capacity. Therefore, this study confirmed that chrysanthemums are potential resources as antioxidants, functional foods, and medicinal materials. Importantly, it may provide a scientific support for further development and utilization of chrysanthemum, and screen excellent varieties for different demands. Abstract :